Evaluation of the Suitability of Irrigated Paddy Fields (Oryza sativa L.) in the Kelingi Irrigation Area, Tugumulyo District, Musi Rawas Regency - Oktaviano Oktaviano; Yuwana Yuwana; Faiz Barchia; Reflis Reflis (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Rice is a strategic staple food whose productivity is influenced by land suitability. This study aims to determine the level of land suitability class for irrigated lowland rice (Oryza sativa L.) in the Kelingi Irrigation Area, Tugumulyo District, Musi Rawas Regency. The study was conducted using a survey method that refers to the level of limiting factors reviewed from land characteristics. Data from field observations and laboratory analysis data were matched with the criteria for land suitability classes for irrigated lowland rice. The actual land suitability class for lowland rice crops is moderately suitable (S2) covering an area of 5,225 ha (51.41%), marginally suitable (S3) covering an area of 4,626 ha (45.52%), while marginally suitable (S3) with a slope of >8% covering an area of 312 ha (3.07%) is recommended for annual crops. The main limiting factors are water availability, land slope class and soil fertility. The limiting factor of soil fertility, still allows for further improvement of its suitability class, by providing balanced fertilizer and to increase the soil pH, agricultural lime can be provided (low input), to overcome the slope of the land, light terracing can be made (medium input), while to overcome water shortages, irrigation channels can be built/rehabilitated.